Imperative role of sugar signaling and transport during drought stress responses in plants. Issue 4 (1st March 2021) - Kaur, Harmeet; Manna, Mrinalini; Thakur, Tanika; Gautam, Vibhav; Salvi, Prafull
Abstract: Cellular sugar status is essentially maintained during normal growth conditions but is impacted negatively during various environmental perturbations. Drought presents one such unfavorable environmental cue that hampers the photosynthetic fixation of carbon into sugars and affects their transport by lowering the cellular osmotic potential. The transport of cellular sugar is facilitated by a specific set of proteins known as sugar transporters. These transporter proteins are the key determinant of influx/ efflux of various sugars and their metabolite intermediates that support the plant growth and developmental process. Abiotic stress and especially drought stress‐mediated injury results in reprogramming of sugar distribution across the cellular and subcellular compartments. Here, we have reviewed the imperative role of sugar accumulation, signaling, and transport under typical and atypical stressful environments. We have discussed the physiological effects of drought on sugar accumulation and transport through different transporter proteins involved in monosaccharide and disaccharide sugar transport. Further, we have illustrated sugar‐mediated signaling and regulation of sugar transporter proteins along with the overall crosstalk of this signaling with the phytohormone module of abiotic stress response under osmotic stress. Overall, the present review highlights the critical role of sugar transport, distribution and signaling in plants under drought stress conditions.